Minimizing Energy Consumption via Sleep Mode in Green Base Station - Saker, Louai; Elayoubi, Salah-Eddine; Chahed, Tijani (2010 IEEE Wireless Communication and Networking Conference, 2010)
In this paper, we develop new energy-efficient, radio resource management schemes for green wireless networks. Our goal is to optimize energy consumption at the network scale while preserving the Quality of Service (QoS) perceived by users. We specifically propose two new sleep mechanisms for base station where a number of resources in system can be shut down for some traffic scenarios in one of two ways: a dynamic way where resources are activated/deactivated in real-time as a function of the instantaneous load of the system, and a semi-static one where resources are kept unchanged during longer time intervals, in the order of one hour. We apply the proposed schemes to 2G and HSPA (High Speed Packet Access) systems and show that the dynamic one achieves larger energy reductions while the semi-static one has an acceptable performance with low complexity.